Penguatan Keputusan Pembelian Melalui Citra Merek: Analisis Pengaruh Inovasi Produk dan Promosi terhadap Kopi Kemiren Jaran Goyang di Banyuwangi - Ramadhani, Bima; Patmi Rahayu, Wening; Churiyah, Madziatul (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the influence of product innovation and promotion on purchasing decisions through brand image as a mediating variable in Kopi Kemiren Jaran Goyang Banyuwangi. Using a quantitative approach and PLS-SEM analysis of 250 respondents, results indicate that promotion significantly affects purchasing decisions directly and indirectly through brand image, while product innovation influences purchasing decisions only through brand image. The study highlights the importance of culture-based branding and digital promotion strategies for MSMEs. These findings offer theoretical contributions to brand equity development and practical insights for enhancing local coffee MSMEs' competitiveness.